Sosialisasi Pengembangan Personal Branding UMKM Desa Murukan Melalui Pelatihan Digital Marketing - Rohmat Hidayat; Septian Ragil Anandita; Siti Nur Qomariyah; Elensya Eka Shintya Putri; Lailatul Firdausi; Laili Ifdhatul Fitri; Siti Anifah (Jumat Ekonomi: Jurnal Pengabdian Masyarakat, 2023)
Personal branding is the process of building a unique personal image and identity for an individual, in this case, the owners of Micro, Small, and Medium Enterprises (MSME) in rural areas. For rural MSME, personal branding can be a powerful tool to enhance their visibility and business image. This community engagement aims to enhance the understanding and skills of rural MSMEs in personal branding, teach digital marketing techniques to MSME so they can effectively promote their products and services on the internet, and promote MSME growth through personal branding strategies and product rebranding training. This activity was conducted on September 4, 2023, involving the subjects of community engagement, the operators of MSME in Murukan Village, Mojoagung, Jombang, which took place in the Murukan Village hall. The method used in this program is Participatory Action Research (PAR) with the following stages: Problem Identification, Joint Planning, Action Implementation, and Reflection and Evaluation. The conclusions of this activity are as follows: (1) The subjects of engagement have begun to understand the importance of Personal Branding: Personal branding plays a crucial role in attracting customers in the competitive digital world. It helps rural MSME differentiate themselves from competitors and build strong customer relationships. (2) Socializing personal branding through digital marketing is done consistently and sustainably in building a brand, requiring time and consistency in messaging and actions as the keys to success. (3) Digital marketing empowers rural MSME to reach a broader audience without incurring significant costs.